Association Between Lower Extremity Venous Insufficiency and Intrapartum Fetal Compromise: A Nationwide Cross-Sectional Study - Asúnsolo, Ángel; Chaowen, Chen; Ortega, Miguel A.; Coca, Santiago; Borrell, Luisa N.; De León-Luis, Juan; García-Honduvilla, Natalio; Álvarez-Mon, Melchor; Buján, Julia (Frontiers in Medicine, 2021)
Introduction: Chronic venous disorder (CVeD) has a very important prevalence, being commonly diagnosed by the presence of varicose veins. The development of varicose veins in lower extremities and/or pelvis venous insufficiency (LEPVI) are frequently. However, its potential impact on fetal health has not been investigated. This study aims to examine whether the presence of varicose veins in women’s lower extremities and/or pelvis is related with intrapartum fetal compromise event. Materials : A cross-sectional, national study was conducted using medical administrative records (CMBD) of all vaginal births (n=256,531) recorded in 2015 in Spain. The independent variable was presence of varicose veins in the legs, vulva, perineum or hemorrhoids. Results: A logistic regression model was used. Among women with vaginal deliveries, women with varicose veins in their lower extremities and/or pelvis have a significantly greater odds of intrapartum fetal compromise (OR=1.30, 95% CI: 1.08-1.54) than their counterparts without varicose veins. After adjustment, this association remained significant (OR=1.25, 95% CI: 1.05-1.50). Conclusions :Our findings of an association between varicose veins in women’s lower extremities and/or pelvis and intrapartum fetal compromise suggest that varicose veins may be a novel and important clinical risk factor for fetal well-being and health.